2006
DOI: 10.1038/sj.ki.5000363
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic acid induces ERK activation via Src SH2 domain association with the epidermal growth factor receptor

Abstract: Within the kidney, angiotensin II type 2 (AT(2)) receptor mediates phospholipase A(2) (PLA(2)) activation, arachidonic acid release, epidermal growth factor (EGF) receptor transactivation, and mitogen-activated protein kinase activation. Arachidonic acid mimics this transactivation by an undetermined mechanism. The role of c-Src in mediating angiotensin II and arachidonic acid signaling was determined by employing immunocomplex kinase assay, Western blotting analysis, and protein immunoblotting on co-precipita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…Indeed, the c-Src inhibitor PP1, inhibited the AVP-induced phosphorylation EGFR at residue 845, whereas the metalloprotease inhibitor GM6001 did not affect the phosphorylation of EGFR at that residue (unpublished results). Similar mechanisms of EGFR transactivation have been previously reported with other GPCR systems [27,[45][46][47][48][49]. On the basis of our coimmunoprecipitation studies we argue that V 1a mediated EGFR transactivation involves the formation of V1a/EGFR complex assembled with β-arrestin 2 and intracellular proteins of the trafficking mechanisms [50].…”
Section: Discussionsupporting
confidence: 52%
“…Indeed, the c-Src inhibitor PP1, inhibited the AVP-induced phosphorylation EGFR at residue 845, whereas the metalloprotease inhibitor GM6001 did not affect the phosphorylation of EGFR at that residue (unpublished results). Similar mechanisms of EGFR transactivation have been previously reported with other GPCR systems [27,[45][46][47][48][49]. On the basis of our coimmunoprecipitation studies we argue that V 1a mediated EGFR transactivation involves the formation of V1a/EGFR complex assembled with β-arrestin 2 and intracellular proteins of the trafficking mechanisms [50].…”
Section: Discussionsupporting
confidence: 52%
“…In some cell lines, Src is responsible for direct activation of the EGFR through phosphorylating essential tyrosine residues on EGFR [37,38]. In renal epithelium, Src tyrosine kinase activation and transactivation of EGFR were found to activate the ERK1/2 pathway in responding to Ang II or arachidonic acid stimulation [11,14]. A physical association of Src and EGFR was observed in these cells under basal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that arachidonic acid mimics Ang II in activation of Src tyrosine kinase, induction of Src and EGFR association via SH2 domain, transactivation of the EGFR tyrosine kinase, activation of small GTPase ras, and activation of downstream ERK1/2 [11,12,14,22]. Experiments were designed to test whether Src and EGFR tyrosine kinases are responsible for mediating H 2 O 2 -induced signaling in these epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Arachidonic acid, in turn, either through cytochrome P450 metabolites or directly, stimulates the ERK pathway. [11][12][13][14][15][16] In sharp contrast to their proposal, however, several studies suggested that Ang II type 1 receptor (AT 1 ) mediates both stimulatory and inhibitory effects of Ang II. 10,17 Our own data obtained from AT 1A -deficient mice also led us to conclude that AT 1 mediates the biphasic regulation in intact mouse proximal tubules.…”
mentioning
confidence: 99%